A technique to control the effect of a spinal support for sitting in patients with a neuromuscular spinal deformity - Gadyatskiy, Oleksandr; Roman, Lyubov; Vasilenko, Irina; Kacher, Vоlоdimir; Chernyshova, Irina (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The use of the authors’ integrated technique with a simultaneous analysis of photos during measurement of the basis vectors of support reactions in patients with neuromuscular diseases in a sitting position by means of basometry makes it possible to assess the results achieved by use of rehabilitation techniques.